(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The process of power generation burning fossile fuels (Coal, Petroleum, and Gas) creates huge environmental problems. This is making scientist and technocrat’s world over attentive to utilize renewable energy sources in power generation and metallurgical industries. Renewable energy sources consist of solar, wind, hydropower, biomass energy etc. while in almost all parts of world biomass energy is found to be most economically viable. All renewable energy sources excepting biomass provide thermal energy only. Biomass is carbonaceous and serves double objective of availability of thermal energy and reduction of oxides. Biomass being the purest fuel produces for less ash in comparison to all other solid fuels including coal. It is estimated that in India, biomass possesses potential for generation of more than 17000 MW of electricity annually. The country is lagging behind to utilize this potential, being able to generate approximately only 2000 MW in spite of Govt. declaration of various incentives. This calls for immediate necessity of producing more power from biomass.In the present work the principle that burning of coal and biomass together (co-firing) offers on excellent an economically variable power generation procedure followed. Non-coking coals (C) from Jharkhand mines were mixed with related biomass (B) species in different ratio (CB= 9010, CB= 8020, CB= 7030, CB= 6040) in order to prepare briquettes.